5t+3=8-2t

Simple and best practice solution for 5t+3=8-2t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5t+3=8-2t equation:


Simplifying
5t + 3 = 8 + -2t

Reorder the terms:
3 + 5t = 8 + -2t

Solving
3 + 5t = 8 + -2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '2t' to each side of the equation.
3 + 5t + 2t = 8 + -2t + 2t

Combine like terms: 5t + 2t = 7t
3 + 7t = 8 + -2t + 2t

Combine like terms: -2t + 2t = 0
3 + 7t = 8 + 0
3 + 7t = 8

Add '-3' to each side of the equation.
3 + -3 + 7t = 8 + -3

Combine like terms: 3 + -3 = 0
0 + 7t = 8 + -3
7t = 8 + -3

Combine like terms: 8 + -3 = 5
7t = 5

Divide each side by '7'.
t = 0.7142857143

Simplifying
t = 0.7142857143

See similar equations:

| 4r+3s+2r=6r+3s | | 7.5(w-2.5)=1.5(3-2w) | | 4x^2-x=-9x | | 13m-27=9m-6 | | -4x-20= | | I=0.4/5 | | 24=X-24 | | (14-2x)(8-2x)=40 | | (x^2)+2t-5=19 | | 7(6y-5(4y-11))=7-8y | | (8x+7)(8x+7)(4x+3)(x+1)=15 | | 3(15x)+7y=208 | | -X-17=3x-1 | | 0.5(6k-0.5)-0.5(3k-0.25)-0.8(5k-2)=0 | | 3(15x)+7x=208 | | -3x-5x-1=0 | | (5ab)(-1/3a)(9b^2) | | Ln(x+2)+5=7 | | sin(6)-sin(42)-sin(66)+sin(78)=-0.5 | | sin(6)-sin(42)-sin(66)+sin(78)=0 | | 0.16=W/5 | | y=4x^3-3x^2+x^6 | | cos(5x)+cos(3x)=cos(x) | | 3logX=9 | | 5-5n=10 | | 6*5/9 | | I=w/V | | 7(4)-7=21 | | I=0.8/5 | | (10x-14)=(5x+56) | | 14(-8x-15)=-1218 | | 10x^2-25x/12=5 |

Equations solver categories